Fabrication and thermal shock resistance of multilayer γ-Y2Si2O7 environmental barrier coating on porous Si3N4 ceramic. Issue 3 (February 2016) - Wang, Chao; Chen, Meng; Wang, Hongjie; Fan, Xingyu; Xia, Hongyan
Abstract: A dense multilayer γ-Y2 Si2 O7 environmental barrier coating was in-situ fabricated by the liquid infiltration and filling method on porous Si3 N4 ceramic for water resistance. When the sintering temperature was 1350 °C, as-prepared coating consisted of the top glass layer, the γ-Y2 Si2 O7 interlayer and the bottom bond layer. With increasing sintering temperature from 1350 to 1450 °C, the microstructure of the coating transformed from three layers into two layers including the γ-Y2 Si2 O7 layer and the bond layer. The γ-Y2 Si2 O7 layer in the coating consisted of γ-Y2 Si2 O7 and Y–Si–Al–O glass, and the γ-Y2 Si2 O7 content increased with the increase of sintering temperature. Thermal shock resistance of the coatings was tested. The results showed that the coating prepared at 1450 °C displayed the better thermal shock resistance. After thermal shock for 15 times from 1000 °C to room temperature, the microstructure of the coating showed little change, and water absorption increased slightly from 4.8% to 5.3%.